Quality evaluation of Xishi Shijian tea based on fingerprint combined with chemical pattern recognition(基于指纹图谱结合化学模式识别的西施石笕茶品质评价) - JIN Ying(金英); HUANG Tiejun(黄铁军); FAN Wenhan(范文含); HE Lezhi(何乐芝); MA Yaping(马亚平); YAO Yijian(姚一建); GONG Shuying(龚淑英); WANG Jiawei(王佳薇); FAN Fangyuan(范方媛) (浙江大学学报. 农业与生命科学版, 2025)
The fingerprints of different grades of Xishi Shijian tea were established by detection of high performance liquid chromatography-fluorescence detector (HPLC-FLD), high performance liquid chromatography-ultraviolet (HPLC-UV) detector, ultrahigh performance liquid chromatography-diode array detector-mass spectrometry/mass spectrometry (UPLC-DAD-MS/MS) and gas chromatography-mass spectrometry (GC-MS). The quality of tea with different grades was evaluated by the combination of fingerprint and chemical pattern recognition. The results indicated that the HPLC-UPLC-GC combination fingerprints of Xishi Shijian tea were established with similarity ranging from 0.616-1.000. A total of 90 common peaks were identified in fingerprints. There were 49 characteristic peaks screened by orthogonal partial least squares-discriminant analysis (OPLS-DA). Furthermore, a total of 41 key chemical components were identified by qualitative and quantitative detections, including 20 taste components and 21 aroma components. The different grades of Xishi Shijian tea exhibited significant variations in key chemical components, which were closely associated with the maturity level of the tea shoot. These differences serve as a crucial material foundation for the discernible disparities in sensory quality. The higher the grade is, the greater the degree of mellow, umami and sweetness, due to its high contents of gallic acids and amino acids, as well as low contents of catechins, flavonoids and caffeine. The presence of alcohols, ketones and alkenes with floral characteristics, such as linalool, β-ionone, and cadin-1 (10), 4-diene, serves as the material basis for the tender and fragrant aroma characteristics found in high-grade samples. In this study, the combination of fingerprints of Xishi Shijian tea and chemical pattern recognition effectively distinguished different grades of tea samples and screened key chemical components, which provides the theoretical basis and technique for the quality evaluation of tea grades.(针对西施石笕茶不同等级样品，采用高效液相色谱-荧光检测器、高效液相色谱-紫外检测器、超高效液相色谱-二极管阵列检测器-串联质谱法以及气相色谱-质谱联用检测法对样品进行检测，构建不同等级西施石笕茶组合指纹图谱，结合化学模式识别法评价西施石笕茶不同等级产品质量。结果表明：本研究建立了西施石笕茶等级样品高效液相色谱-超高效液相色谱-气相色谱组合图谱，相似度范围为0.616～1.000，共标定90个共有峰。进一步利用化学识别正交偏最小二乘判别分析筛选出49个特征峰，并通过定性和定量检测指认41个关键化学组分，包括20个滋味组分和21个香气组分。关键化学组分在不同等级样品中的含量有明显差异，这与原料成熟度密切相关，是不同等级样品感官品质差异表现的重要物质基础。高含量没食子酸、氨基酸，与较低含量的儿茶素类、黄酮类以及咖啡碱是高等级样品滋味表现出鲜醇甘润特征的重要原因；而具有花香特征的芳樟醇、β-紫罗兰酮、卡达-1（10），4-二烯等醇类，酮类及烯类是高等级样品呈现嫩香、馥郁特征的物质基础。本研究构建的不同等级西施石笕茶组合指纹图谱结合化学模式识别法，能够有效区分不同等级样品、筛选关键化学组分，为茶叶等级样品质量评价提供了理论依据及技术手段。)